Role of Diffusion Weighted MRI in Assessment of Deep Myometrial Invasion by Endometrial Tumor-Comparing with Histopathology (Medical Forum Monthly, 2024)
ABSTRACTObjective: To evaluate the diagnostic accuracy of Diffusion Weighted Magnetic Resonance Imaging in Assessment of deep myometrial invasion by endometrial tumor, taking histopathology as a gold standard.Study Design: cross sectional study.Place and Duration of Study: This study was conducted at the Department of Diagnostic Imaging in Nishtar Hospital, Multan, Pakistan from October 2016 to October 2018.Materials and Methods: Total 75 patients having endometrial carcinoma, ages between 20-60 years were included. Patients with previous uterine surgery, receiving radiotherapy and chemotherapy, claustrophobia and cardiac pacemakers were excluded. Diffusion weighted MRI of the abdomen and pelvis was done in all. DW-MRI finding were interpreted by consultant radiologist for presence or absence of deep myometrial invasion. After surgery specimenswere sent to the institutional pathology laboratory for histopathology.MRI findings were compared with histopathology. Data was analyzed using SPSS-18. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated.Results: Total 75 patients fulfilling inclusion criteria were included. 38 (True Positive) had deep myometrial invasion on histopathology. Among 35DW-MRI negative patients ,01 (false negative) had deep myometrial invasion on histopathology (p=0-0001). Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of diffusion weighted imaging in assessment of deep myometrial invasion by endometrial tumor, taking histopathology as gold standard was 97.43%,94.44%,95.00%,97.14% and 96.00% respectively.Conclusion: Study concluded that DW-MRI is a highly sensitive and accurate noninvasive modality for diagnosing deep myometrial invasion by endometrial tumor.